Ultrafast Response p‐Si/n‐ZnO Heterojunction Ultraviolet Detector Based on Pyro‐Phototronic Effect. Issue 32 (24th May 2016) - Wang, Zhaona; Yu, Ruomeng; Wang, Xingfu; Wu, Wenzhuo; Wang, Zhong Lin
Abstract : A light‐self‐induced pyro‐phototronic effect in wurtzite ZnO nanowires is proposed as an effective approach to achieve ultrafast response ultraviolet sensing in p‐Si/n‐ZnO heterostructures. The relatively long response/recovery time of zinc‐oxide‐based ultraviolet sensors in air/vacuum has long been an obstacle to developing such detectors for practical applications. The response/recovery time and photoresponsivity are greatly improved by the pyro‐phototronic effect.